Pemanfaatan Limbah Jagung Sebagai Substrat Dalam Menghasilkan Poli-Β-Hidroksi Butirat (Phb) Oleh Isolat Bakteri Asal Pabrik Gula Arasoe Bone - NUR HAEDAR; SRI NUR RAHMI; ASADI ABDULLAH (Prosiding Seminar Biologi, 2016)
The research about Waste of Corn as Substrate In Produce Poly-β-Hydroxy Butyrate (PHB) by Bacterial Isolates Origin Sugar Factory Arasoe Bone. The research purpose to determine the ability of bacterial isolates from sugar mills Arasoe Bone is BA9 and MA4 and nitrogen concentration optimal for producing the PHB. With usewaste of corn as a source of carbon with a concentration 1%, 2%, 3% and as control positive glucose 1%, as well as use of ammonium sulfate as nitrogen source at a concentration of 0.05%, 0.1% and 0.15%. Total Analysis of PHB done with use UV-VIS spectrophotometer and a wavelength of 235 nm and using analysis a regression equation. The result of this study that use of corn as a source of carbon waste can produce PHB either by BA9 and MA4 isolates though still lower than glucose as the carbon source. The concentration of nitrogen source (ammonium sulfate), which accumulate PHB optimal concentration of ammonium sulfate that is at 0.1%. Keywords: Poly-β-hydroxy butyrate (PHB), Bacterial Isolates, Waste Corn, incubation time, the waste sugar factory